Periaqueductal/periventricular gray deep brain stimulation for the treatment of neuropathic facial pain - Mandat, Victor; Zdunek, Pawel R.; Krolicki, Bartosz; Szalecki, Krzysztof; Koziara, Henryk M.; Ciecierski, Konrad; Mandat, Tomasz S. (Frontiers in Neurology, 2023)
The Periaqueductal gray (PAG) and the periventricular gray (PVG) are the anatomical targets for deep brain stimulation (DBS) to treat refractory neuropathic pain. Methods: 7 (4 female and 3 male) patients were qualified for PAG/PVG DBS because of neuropathic facial pain. Frame-based unilateral implantations of DBS were conducted according to indirect planning of the PAG/PVG, contralateral to reported pain (3389, Activa SC 37603, Medtronic). The efficacy of PAG/PVG DBS on pain was measured with Numeric Pain Rating Scale (NRS) and Neuropathic Pain Symptom Inventory (NPSI) before surgery and three, twelve, and 24 months after surgery.Results: The mean age of the group at the implantation was 43,7 years (range: 28-62; SD: 12,13). The mean duration of pain varied from 2 to 12 years (mean: 7,3; SD: 4,11). Five patients suffered from left-sided facial pain and two suffered right-sided facial pain. The aetiology of pain among four patients was connected to ischemic brain stroke and in one patient to cerebral hemorrhagic stroke. Patients did not suffer from any other chronic medical condition The beginnings of ailments among two patients were related to craniofacial injury. NRS decreased by 54% at the three months follow-up. The efficacy of the treatment measured with mean NRS decreased at one-year follow-up to 48% and to 45% at 24 months follow-up. The efficacy of the treatment measured with NPSI decreased from 0,27 to 0,17 at two years follow-up (mean reduction by 38%). The most significant improvement was recorded in the first section of NPSI (q1: burning-reduced by 53%). The records of the last section (number five) of the NPSI (paresthesia/ dysesthesia-Q11/Q12) have shown aggravation of those symptoms by 10% at the two-years follow-up. No surgeryor hardware-related complications were reported in the group. Transient adverse effects related to the stimulation were eliminated during the programming sessions.Conclusions: PAG/PVG DBS is an effective and safe method of treatment of medically refractory neuropathic facial pain. The effectiveness of the treatment tends to decrease at two years follow-up. The clinical symptoms which tend to respond the best is burning pain.Symptoms like paresthesia and dysesthesia might increase after DBS treatment, even without active stimulation.